Penyelenggaraan Teknis dan Administrasi Dana Desa dalam Menunjang Pembangunan Kampung-Kampung di Distrik Supiori Papua - Rosa Mual (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2022)
The current study was designed to examine the allocation of village funds as an effort to develop the village, especially in East Supiori Regency as a district propagation. In addition, this research also seeks to examine the various factors that influence and hinder the management of village fund allocations. This type of research was empirical-juridical research. The final research found that the administration and technical implementation of village funds in supporting village development in Sorendiweri Village, East Supiori District Papua had been running according to established procedures. The implementation begins with planning rules and accountability reports. At the planning stage, each component that is included in the ranks of the government is also present to discuss the amount of the budget that will be issued as a form of transparency. Planning includes all kinds of funds that will be used in the following year. The inhibiting factor in the development is the geographical location which is difficult to reach and lacks of capable human resources, so it takes quite a long time.